Phone Snubbing Behavior and Social Interactions of Muslim Students - Hidayat, Bahril; Reza, Iredho Fani; Arief, Yanwar; Rizki, Rinjani Ayu; Iskandar, Willem (UIR Press, 2025)
This research aims to determine the relationship between phone snubbing (phubbing) behavior and social interaction. This research method is correlational quantitative. The subjects of this study were students as if the High School and were 11th grade students. The number of subjects was 181 students who were selected using purposive sampling technique. The instruments used are the phubbing behavior scale and the social interaction scale. Data analysis using SPSS version 26 for windows. The results of the hypothesis test showed a significance value of 0.000 p < 0.05, with Pearson-Correlation -0,583. It can be concluded that there is a negative relationship between phubbing behavior and social interaction of high school students. So that the hypothesis proposed in this study can be accepted. Based on the categorization of phubbing behavior variable scores, it can be concluded that 26 students (14%) fall into the low category, 127 students (71%) are in medium category, and 28 students (15%) are in the high category. This indicates that the majority of students exhibit a moderate level of phubbing behavior.